RANCANGAN BUKU KERJA PENGUATAN PENGETAHUAN MATERI BAGI GURU IPA SMP - Anggrainy, Cindy; Natalina, Mariani; Suryawati, Evi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Technological Pedagogical and Content Knowledge (TPACK) is a conceptual framework that shows the relationship between the three realms of knowledge required by the teacher: technological knowledge, pedagogical knowledge, and content knowledge. The purpose of this research is to develop a workbook for the strengthening of content knowledge for science teachers of SMP. The workbook was developed from the essential indicator of Teacher Competency Test (UKG). Stage design, development, internal validation and simulation workbook trials conducted in Biology Education Laboratory FKIP University of Riau. External validation and limited trials were conducted at MGMP IPA Pekanbaru City. Workbooks are validated with four aspects of technology knowledge ie format, content, illustrations, and language. The result of the validation of all aspects shows that the workbook is in a very valid category. Workbooks can be used as learning resources by teachers to improve the professional competence of teachers in teaching and learning.Key Word : Science for SMP, Content Knowledge, Workbook